Toward an Improved Understanding for Design of Material Extrusion Additive Manufacturing Process‐Based 3D Printers—a Computational Study. Issue 1 (18th November 2022) - Singhal, Ishant; Tyagi, Bobby; Chaudhary, Riya; Sahai, Ankit; Fayazfar, Haniyeh; Sharma, Rahul Swarup
Abstract: Understanding and improving 3D printing process models are very important for designing building defect‐free 3D printers. Most studies have failed to present detailed process design and modeling of material extrusion (MatEx)‐based additive manufacturing (AM) in a systematic approach that considers all process parameters such as nozzle diameter, nozzle angle, and velocity. It is studied that the accuracy and consistency of a MatEx 3D fabricated product depend on the pressure drop across various nozzle zones. This paper identifies the constraints affecting the performance of the MatEx AM process and presents mathematical modeling related to various process parameters. Also, the paper shows expressions for pinch wheel feed mechanism, liquefier, and nozzle geometry of the MatEx process in terms of independent variables, such as liquefier temperature, nozzle geometry, and feed rate. This will be helpful in computing the precise design parameters of MatEx‐based 3D printers. The complex mathematical expressions developed are pivotal for the effective regulation of the 3D printing process. It not only provides new and better designs for MatEx machines with precise operation and better resolution but also opens the scope for further scientific development to expand the capability of proposed approach for both specific applications and the field. Abstract : The work described in this paper involves developing the equations for various parameters of the MatEx AM process in a structured manner along with providing information about the constraints and assumptions of the derivation process, the data regarding variation in the parameters with respect to nozzle geometry, and in turn developing a computational model governing the MatEx AM process which would eliminate design constraints and limitations of this process.